Subsequent primary malignancies among multiple myeloma patients treated with or without lenalidomide. Issue 3 (4th March 2017) - Rollison, Dana E.; Komrokji, Rami; Lee, Ji-Hyun; Hampras, Shalaka; Fulp, William; Fisher, Kate; Baz, Rachid; Nishihori, Taiga; Xu, Qiang; Olesnyckyj, Marta; Kenvin, Laurie; Knight, Robert; et al.
Abstract: Risk of subsequent primary malignancies (SPMs) associated with lenalidomide therapy in multiple myeloma (MM) patients, outside the context of melphalan-based therapy is not established. We assessed the risk of SPMs in lenalidomide treated MM patients ( n = 1653) at Moffitt Cancer Center (2004–2012) outside the context of melphalan-based induction therapy and post-melphalan maintenance therapy, via (1) cohort analysis and (2) nested case-control study. Incident SPMs ( n = 51) were matched to controls ( n = 102) on age at MM diagnosis, gender, follow-up time, and date of diagnosis. Incidence of SPM differed significantly ( p = 0.0038) between MM patients treated with and without lenalidomide (5-year incidence estimates of 3.2 and 6.2%, respectively), although not significant after adjustment for age and year of diagnosis (HR = 0.82, 95%CI = 0.43–1.57). Lenalidomide treatment was inversely associated with SPM in the nested case-control analysis (OR = 0.03, 95%CI = 0.002–0.34). In this large cohort of MM patients, lenalidomide treatment was not associated with an increased risk of SPM.